More than dollars and cents: Putting a price on indwelling pleural catheter drainage - George, V; Rahman, NM (American Thoracic Society, 2020)
Malignant pleural effusions (MPEs) are common and seen in up to 15% of patients with cancer (1). They are estimated to affect over 150,000 people per year in the United States, and this is projected to increase as the global incidence of cancer rises and patients’ life expectancy improves (2, 3).